STRATEGIES FOR SUSTAINABLE DEVELOPMENT OF LIVESTOCK FARMING IN DESERT REGIONS UNDER CLIMATE CHANGE CONDITIONS - Nurmanov , Sherzod (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
This scientific thesis provides an in-depth analysis of integrated strategies for the sustainable development of livestock farming in Uzbekistan’s desert and semi-desert regions under climate change conditions. It examines the direct and indirect impacts of climate change (heat stress, pasture degradation, water scarcity, and soil salinization) that reduce livestock productivity and threaten food security. The thesis proposes adaptation strategies including genetic selection of heat- and drought-resistant local breeds, rotational grazing management, water-efficient technologies, agro-pastoral integration, and precision livestock farming. Based on scientific models and national statistics, pathways to ensure the ecological, economic, and social sustainability of livestock farming are outlined. The results demonstrate that livestock farming in desert areas can be transformed into a carbon-neutral and resource-efficient system.